Development Of Fitting Kit Using Augmented Reality For Fitting Skill Subject At Vocational College - Ismail, Mohd Erfy; Hamzah, Hasyimah; Ismail, Irwan Mahazir; Masran, Saiful Hadi; Marian, Mohd Fairuz (Online Journal for TVET Practitioners, 2017)
The rapid development of Information Technology today has given a new impetus to the use of technology, especially in the field of education. One of the developments that are increasingly popular nowadays is Augmented reality (AR) which use a barcode scanning technology as a medium of learning. This study aims to build an interactive multimedia-based teaching and learning theory and appriopate design based on Fitting Skill syllabus for Vocational College. Factors that contributed to this study is, teaching methods, the learning process safety, visualization and lack of teaching aids in the Fitting Skills subject. For the development of Fitting Kit, researcher used the ADDIE model as a reference and guide. The population included 150 students Machining Industry in KV Kluang and the sample is 30 first-year students in Machining Industry courses which take the Fitting Skill subject. To obtain information in this research, researcher used questionnaire as an instrument. Data was collected and analyzed using SPSS (Statistical Package for the Social Sciences) version 24. Based on the analysis made, the reliability of the instrument is r = 0.86 and showed that the reliability of the instrument is at high level. The results showed that the use of interactive multimedia aided AR can increase student interest and thereby making the teaching more attractive in addition to improve existing ABBM. In addition, the findings show that the use of AR in education can improve visualization of the students which are able to assist them in carrying out